Los Mochicas Una civilización compleja - Colque Cruz, Ivonne Carola (Facultad de Ciencias Jurídicas y Políticas - Universidad Nacional del Altiplano de Puno, 2023)
The Moche culture, also known as Mochica, developed in the Early Intermediate Period of Ancient Peru, approximately in the 1st and 7th centuries. It was a civilization that existed on the north coast of Peru and in the Moche valley. Standing out for its hydraulic inventions, its monumental architecture, its exquisite artistic development, especially in the fields of goldsmithing and ceramics.During the heyday of the Mochica culture, they carried out very important architectural works, also known as huacas,which have endured over time, becoming part of a cultural and ancestral legacy.The Mochicas had made the desert Peruvian coast their home, but as a result of the terrible meteorological phenomenon known as El Niño, which occurred at the end of the 7th century, ruining the Mochica's way of life, even many of the inhabitants began to fall ill. In addition, it weakened the political organization, since many of the leaders started internal wars, which led to the end of the Mochica states.